Analisis Viral Marketing, Harga, dan Kualitas Produk Terhadap Keputusan Pembelian Skincare - Ari Anggara Pribadi; Hennywati; Kayla Putri Rindha (STKIP MAJENANG, 2023)
This study was conducted to analyze the influence of viral marketing, price, and product quality on skincare purchasing decisions. In this research, data were obtained using the literature review method. The results show that viral marketing, leveraging social media and influencer engagement, has a significant impact on increasing product visibility and attracting consumer interest. Price, while being a factor considered, has a varying influence depending on consumers' perceptions of the balance between price and quality. Product quality was found to be the dominant factor affecting purchasing decisions, as consumers generally prefer products that are safe, effective, and meet their needs. These conclusions emphasize the importance of effective marketing strategies and product quality improvements to meet consumer preferences and foster their loyalty.